2017
DOI: 10.1111/myc.12636
|View full text |Cite
|
Sign up to set email alerts
|

The changing trends and profile of pneumocystosis mortality in the United States, 1999‐2014

Abstract: Pneumocystosis (PCP) mortality in the U.S. has received less attention in recent years. This study describes recent trends in mortality and the estimated burden of PCP in the U.S., using the national multiple cause of death data during 1999-2014. PCP mortality rates were calculated for age, sex, race and year. Demographic differences were presented for decedents with and without a human immunodeficiency virus (HIV) co-diagnosis. Matched odds ratios (MOR) were generated to describe associations between non-HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Therefore, it may be inferred that the combination therapy with caspofungin can compensate for the defects of TMP/SMZ in patients with delayed PJP treatment. 3Increasing evidence of mutations in the genes that encode dihydropteroate synthase may lead to drug resistance of sulfa agents, and several studies have demonstrated that it was associated with treatment failure (Wickramasekaran et al, 2017;Nahimana et al, 2003). With the attention paid to the prevention of PJP, long-term oral administration of TMP/SMZ may increase the risk of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it may be inferred that the combination therapy with caspofungin can compensate for the defects of TMP/SMZ in patients with delayed PJP treatment. 3Increasing evidence of mutations in the genes that encode dihydropteroate synthase may lead to drug resistance of sulfa agents, and several studies have demonstrated that it was associated with treatment failure (Wickramasekaran et al, 2017;Nahimana et al, 2003). With the attention paid to the prevention of PJP, long-term oral administration of TMP/SMZ may increase the risk of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The first-line therapy of PJP is TMP/SMZ (trimethoprim/ sulfamethoxazole), which has remained unchanged for many years (White et al, 2017;Wickramasekaran et al, 2017;Roembke et al, 2014). However, about 25% of patients cannot complete the full course of the TMP/SMZ regimen because of treatment failure or various side effects such as marrow suppression, renal damage, gastrointestinal upset and so on (Benfield et al, 2008).…”
mentioning
confidence: 99%
“…This has important implications when designing diagnostic tools and new treatment strategies for infected patients. While PCP is recognised as an AIDS-defining illness, the increased incidence in non-HIV patients is alarming and warrants the need for improved diagnostic and treatment strategies for affected patients [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…Invasive fungal infections (IFIs) are a leading cause of morbidity in immunocompromised people, including those living with HIV (PLHIV) . Pathogenic fungi are responsible for a variety of syndromes in PLHIV, such infections can develop into life‐threatening conditions .…”
Section: Introductionmentioning
confidence: 99%